COMPARATIVE MICROMORPHOLOGY LEAF SURFACE OF SELECTED HOYA SPP. (APOCYNACEAE) FROM SARAWAK - Ridzuan, Khaleeda; Kalu, Meekiong (Research Center for Biology, 2023)
Traditionally, morphological parameters have been used for several taxonomic and ecological identifications. The morphological characteristics alone would be difficult to distinguish the evidence for species identification. Hence, a study of leaf anatomy was conducted to compare the structural characteristics which focused on the epidermal cells, stomata, and trichomes by using a Compound Microscope and Scanning Electron Microscope (SEM). Four selected species of Hoya from various localities within western of Sarawak were studied: H. caudata, H. coronaria, H. omlorii, and H. verticillata. The results showed stomatal types of Hoya species have stephanocytic stomata, except for two species which have slightly significant differences: H. coronaria has anomocytic stomata and H. omlorii has paracytic stomata. Meanwhile, in terms of the stomatal presence, all species possessed hypostomatic stomata, only H. verticillata has amphistomatic stomata which stomata presence on both sides of the adaxial and abaxial surfaces. Highest stomatal density was recorded in H. omlorii whereas the lowest were recorded in H. coronaria. Stomatal index were calculated and H. caudata has the highest with 12.80% and H. coronaria has the lowest value which is 6.28%. All four species were completely absence of trichomes except for H. coronaria which has simple unicellular non-glandular trichomes. The result indicates that the anatomical characteristics provide additional information and could be a great assist in the distinction within Hoya species.